Antenatal Periviability Counseling and Decision Making: A Retrospective Examination by the Investigating Neonatal Decisions for Extremely Early Deliveries Study Group - Feltman, Dalia M.; Fritz, Katie A.; Datta, Avisek; Carlos, Christine; Hayslett, Drew; Tonismae, Tiffany; Lawrence, Christin; Batton, Emily; Coleman, Tasha; Jain, Meenu; Andrews, Bree; Famuyide, Mobolaji; Tucker Edmonds, Brownsyne; Laventhal, Naomi; Leuthner, Steven (American Journal of Perinatology, 2020)
Objective To describe periviability counseling practices and decision making.Study Design This is a retrospective review of mothers and newborns delivering between 22 and 24 completed weeks from 2011 to 2015 at six U.S. centers. Maternal and fetal/neonatal clinical and maternal sociodemographic data from medical records and geocoded sociodemographic information were collected. Separate analyses examined characteristics surrounding receiving neonatology consultation; planning neonatal resuscitation; and centers' planned resuscitation rates.Results Neonatology consultations were documented for 40, 63, and 72% of 498 mothers delivering at 22, 23, and 24 weeks, respectively. Consult versus no-consult mothers had longer median admission-to-delivery intervals (58.7 vs. 8.7 h, p < 0.001). Consultations were seen more frequently when parental decision making was evident. In total, 76% of mothers had neonatal resuscitation planned. Resuscitation versus no-resuscitation newborns had higher mean gestational ages (24.0 vs. 22.9 weeks, p < 0.001) and birthweights (618 vs. 469 g, p < 0.001). Planned resuscitation rates differed at higher (HR) versus lower (LR) rate centers at 22 (43 vs. 7%, p < 0.001) and 23 (85 vs. 58%, p < 0.001) weeks. HR versus LR centers' populations had more socioeconomic hardship markers but fewer social work consultations (odds ratio: 0.31; confidence interval: 0.15–0.59, p < 0.001).Conclusion Areas requiring improvement included delivery/content of neonatology consultations, social work support, consideration of centers' patient populations, and opportunities for shared decisions.
Keywords: neonatology; race; decision making